2022
DOI: 10.1097/hjh.0000000000003108
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension determinants among Ghanaians differ according to location of residence: RODAM study

Abstract: van den Born a,b , and Charles Agyemang a Objective: Hypertension prevalence is high among African migrants, but the determinants of hypertension in migrants in Europe in relation to the population in the country of origin still needs to be elucidated. Therefore, the aim of this study was to assess the determinants of hypertension in Ghanaians residing in Ghana and Europe. Methods:The current study used baseline data of 5659 participants, aged 25-70 years, of the Research on Obesity and Diabetes among African … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…23 24 The RODAM study has identified various cross-sectional factors associated with CVD risk factors. [25][26][27] In addition, the study has resulted in the first EWAS for type 2 diabetes in SSA, in which we identified several CpG sites that were differentially methylated between type 2 diabetes cases and controls at an epigenome-wide level. 28 In our study of epigenome-wide DNA methylation differences between migrant and non-migrant Ghanaians, we identified 13 differentially methylated positions and 3 differentially methylated regions between migrants and non-migrants, with DNA methylation differences ranging from 0.1 to 4.5%.…”
Section: Findings To Datementioning
confidence: 99%
“…23 24 The RODAM study has identified various cross-sectional factors associated with CVD risk factors. [25][26][27] In addition, the study has resulted in the first EWAS for type 2 diabetes in SSA, in which we identified several CpG sites that were differentially methylated between type 2 diabetes cases and controls at an epigenome-wide level. 28 In our study of epigenome-wide DNA methylation differences between migrant and non-migrant Ghanaians, we identified 13 differentially methylated positions and 3 differentially methylated regions between migrants and non-migrants, with DNA methylation differences ranging from 0.1 to 4.5%.…”
Section: Findings To Datementioning
confidence: 99%
“…Thirteen risk factors were initially assessed based on the literature review, 3,7,[23][24][25] clinical understanding of hypertension, and empirical evidence of factors associated with hypertension in the SIREN dataset. 7 Briefly, these factors were identified/ defined as follows: sex (male or female), age (<65 or ≥65) years, residence (rural or urban), formal education completed ("none" or "at least primary school"), physical inactivity (where the respondent was not involved in physical exercise including walking, swimming, gardening, jogging, playing football, and vigorous exercise for <4 hours/week 26 ), current alcohol use (self-reported; no or yes), current smoking (using any form of tobacco products for at least 12 months before the time of recruitment 19 ), adding salt at the table to ready-to-eat meals (self-reported; no or yes), anthropometric measurements (body mass index [BMI] and waist circumference [WC] measured by trained personnel using standard protocols), and family history of CVD (self-reported; no or yes).…”
Section: Identification and Assessment Of Risk Factorsmentioning
confidence: 99%